Effects of different rootstocks on the morphologic parameters of watermelon grafts during transplant production - Horváth, D. E.; Takácsné Hájos, M. (International Journal of Horticultural Science, 2013)
Before Hungary joined the EU watermelon production was a key sector of the Hungarian vegetable industry. Its production area shrank by nearly 60 % since 2004, it is only 5000 ha today. Stable and reliable market failed to evolve in the last years and extreme weather events occurred more frequently. An unfavourable growing season can notably affect the production volume of the next season. Information gathered in the last years support the assumption, that suitable stocks can help eliminate the issues caused by extreme weather or short-term crop rotation. Choosing the right grafted or non-grafted transplant is not enough any more, growers also have to select stock. In fruit and vine production choosing the stock, which is the most suitable for the technology is evident and this approach should be widely adapted by watermelon growers as well. In this research we investigated the growth parameters of different watermelon stocks and their effect on the scion during the transplant production. Measurements were carried out on seven different stock-scion combinations of the scion ’Topgun F1’ hybrid. Two of the stocks were interspecific (Cucurbita maxima × Cucurbita moschata) and five stocks were Lagenaria-type (Lagenaria siceraria) stocks. We made and recorded observations of the transplants’ length (cm), diameter of the stock and scion (mm), number of leaves (piece), root length (cm), root mass (g) and shoot mass (g). We concluded that early pricking out of transplants with interspecific stocks is successful due to their hardiness and vigorous growth. The effect of the ’Shintosa camelforce F1’ interspecific stock was outstanding. Furthermore, the results confirmed the practical observation that the root system of interspecific stocks grow vertically more allowing them to take up water and nutrients from lower soil layers in poor sandy soils. From the Lagenaria group the root system of the ’DG-01 F1’ was similar to the interspecific stocks’. It can be grown even in sandy soil, however other Lagenaria-type stocks are more suitable for production in hard soils with nutrient supply because of their compact root system. This study can serve as a basis for further research in the topic that can conduce to site- and technology-specific stock selection.